The Extent to which Dimensions of Coping Skills in Subjective Well-being are Explained among a Sample of Retired Senior Military Officers in the Hashemite Kingdom of Jordan - Al Garalleh , Abdul Nasser Musa (Dirasat: Educational Sciences, 2021)
The current study aims to investigate the extent to which dimensions of coping skills in subjective well-being are explained among a sample of retired senior military officers in the Hashemite Kingdom of Jordan. To achieve the objectives of the study, a sample was selected from the Military Retirees Institution in Karak Governorate, with (236) retired senior military officers. Two scales were developed: the coexistence skills scale and the self-contentment scale; their psychometric properties were verified. The study was applied at the beginning of the year (2019) to the sample members. A descriptive-predictive methodology was used. The results showed that the level of possession of coexistence skills among senior retired military officers was medium in total, and ranged between medium and high in some dimensions. The skills of coexistence explain about (9.5%) of the subjective well-being and that the skills of coexistence and subjective well-being do not differ according to military rank. Based on the results, the study recommends paying attention to retired senior military officers and working to improve their coexistence and subjective well-being skills.